2002
DOI: 10.1038/sj.bmt.1703661
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring cytomegalovirus infection by antigenemia assay and two distinct plasma real-time PCR methods after hematopoietic stem cell transplantation

Abstract: Summary:We compared a CMV virus load determined by realtime PCR with an antigenemia value to analyze the correlation between these two methods. We also compared the values for virus load determined by the two distinct real-time PCR methods, which amplify the US17 region and immediate-early (IE) gene of CMV, respectively, to evaluate the reliability of these methods. Two hundred and sixty-five samples were obtained weekly from 29 patients, who had engraftment after unrelated bone marrow transplantation or HLA-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
31
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 23 publications
5
31
0
1
Order By: Relevance
“…Results for all combinations of genomic regions correlated well. Tanaka et al 15 reported that US17-PCR showed a higher (approximately three--10-fold) viral load than IE-PCR. But this trend was not demonstrated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Results for all combinations of genomic regions correlated well. Tanaka et al 15 reported that US17-PCR showed a higher (approximately three--10-fold) viral load than IE-PCR. But this trend was not demonstrated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The antigenemia assay, however, requires rapid processing of specimens, is labor-intensive, cannot be automated, is subjective in reading, and is unfeasible during periods of severe neutropenia. In addition, it does not reflect the viral load in the blood compartment accurately (12) and sometimes displays negative results in the presence of CMV disease (2,31,32,36).Quantification of CMV DNA in blood by PCR is emerging as an alternative to the antigenemia assay and may soon become the standard for the surveillance of CMV infection in Allo-SCT recipients. Viral load quantification in blood allows early detection of active CMV infection, close monitoring of the response to antivirals, prediction of the risk of viremic relapse, emergence of resistant strains, and eventual development of CMV disease (8,31).…”
mentioning
confidence: 99%
“…The antigenemia assay, however, requires rapid processing of specimens, is labor-intensive, cannot be automated, is subjective in reading, and is unfeasible during periods of severe neutropenia. In addition, it does not reflect the viral load in the blood compartment accurately (12) and sometimes displays negative results in the presence of CMV disease (2,31,32,36).…”
mentioning
confidence: 99%
“…When input concentration was 2,500 to 5,000 copies/ml, the sensitivity of nested PCR was 47.3%, while sensitivity was (21). Therefore, we compared the nested PCR protocols being used at our institution with results obtained by using the most popular primers in real-time PCR assays.…”
Section: Discussionmentioning
confidence: 99%